PEMBELAJARAN MATEMATIKA REALISTIK PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT BAGI SISWA KELAS IV SEKOLAH DASAR - Rissa Prima Kurniawati (Universitas PGRI Madiun, 2015)
Mathematics has characteristic in good abstract object. That cause students have difficulty in understanding of mathematics. Therefore, the real-life experiences of children in the classroom are important for learning and students will understand the material quickly. This study is aimed to describe the activities of students during the learning process that takes place in the material realistic arithmetic addition and subtraction and describe the learning completeness students after being taught with realistic learning the material arithmetic addition and subtraction of integers. This type of research used in this research is qualitative research. Subjects in this study were students of class IV SDN Jenangan, Kwadungan, Ngawi.Based on this research, student activities relevant to teaching (teaching and learning) of 98.83% classified in the category very well. While the student activity which is not relevant to the teaching of 10.15%. Completeness students in realistic mathematics learning on the material arithmetic operations of addition and subtraction of integers for fourth grade students of SDN Jenangan, Kwadungan, Ngawi gained mastery learning students individually sebannyak 12 students from the number of students as many as 15 students altogether, which is not completed individually as 3 students. While the classical completeness, acquired 80% of students who completed study.